What's Special About Counselling Older Women? - Crose, Royda (Canadian Journal of Counselling and Psychotherapy, 2011)
This paper emphasizes the need for the feminization of geriatric mental health and calls attention to some special issues for women in later life. The older woman who seeks mental health services may well be warned that "counselling could be hazardous to her health!" Few mental health professionals are knowledgeable about gender differences in development or about late life development and aging processes. Therapists who are not trained in these areas tend to rely on their own personal experience with older persons, both positive and negative, resulting in a number of countertransference issues for the therapist.